Transport Development Priorities in Papua and West Papua - World Bank (World Bank, 2012)
The province of Papua of the Republic of Indonesia was provided special autonomy under law 21-2001 in recognition of the fact that 'the management and use of the natural wealth of Tanah Papua has not yet been optimally utilized to enhance the living standard of the natives, causing a deep gap between the Papua province and the other regions, and violations of the basic rights of the Papuan people.' The goal of special autonomy was to help Papua and Papuans catch up to the rest of Indonesia in terms of living standards and opportunities. Yet, now almost a decade later, and after the split into two provinces: Papua and West Papua, progress toward this goal has been slow. In recognition of this, the Indonesian central government issued presidential instruction 5-2007 on the acceleration of development of Papua and West Papua instructing all relevant technical ministries to devote special attention to the two provinces and to coordinate their programs with the governors of both provinces. Transport is a key piece of the development puzzle and is a high priority for all levels of government in Papua and West Papua. Yet, despite this, and large amounts of investment channeled toward the sector, the people of Papua and West Papua are not receiving substantially better transportation services than they were before special autonomy. This report aims to set out a set of priorities that transport development must follow in Papua and West Papua if investments are to be productive and remain useful for their entire design life.